Short‐term intraperitoneal catheters: An ambulatory care intervention for refractory ascites secondary to cirrhosis during COVID‐19. Issue 10 (1st September 2021) - Ngu, Natalie LY; Anderson, Patricia; Hunter, Jo; Figredo, Anita; Papaluca, Timothy; Pianko, Stephen; Dev, Anouk; Bell, Sally; Le, Suong
Abstract: Background and Aim: Patients with refractory ascites have frequent hospital admissions, which pose exposure risks in the context of the COVID‐19 pandemic. The aim of this study was to investigate the safety and efficacy of a novel 12‐week, multidisciplinary ambulatory care program allowing frequent low‐volume ascitic drainage through a tunneled, intraperitoneal catheter (IPC). Methods: Adult patients with cirrhosis complicated by refractory ascites were recruited through a liver clinic in a tertiary health service in Melbourne, Australia from April to December 2020. All patients were enrolled in a 12‐week multidisciplinary program including medical, nursing, dietetics, and pharmacy support. A Rocket Medical IPC was inserted on day 1 with 1–2 L of ascitic fluid drained over 1–3 sessions per week either at the patients' homes or at the hospital day ward. Patients' demographics, death, complications, and self‐reported outcomes were recorded. Results: Twelve patients were enrolled with a median of 65‐day (interquartile range [IQR]: 16.5–93) IPC duration between April and December 2020 across two periods of COVID‐related lockdown in Melbourne, Australia. There were no IPC‐related deaths. Early removal was necessitated in three patients due to leakage, nonadherence, and bacteremia. On day 30, the median self‐reported health score increased from 50 (IQR: 50–70) to 78 (IQR: 50–85), attributable to a reduction in symptom burden. Conclusion: A multidisciplinary IPC program including the use of short‐term IPC was safe and associated with a self‐reported improvement in perceptions of health. In the context of the COVID‐19 pandemic, the program aimed to reduce patient and clinician exposure, which is maintaining engagement and management of decompensated cirrhosis. Abstract : Management of refractory cirrhotic ascites poses exposure risks in the context of the COVID‐19 pandemic. We found that short‐term intraperitoneal catheters as part of a home‐based multidisciplinary program were safe and associated with improvement in self‐reported health perception.